Electrical Curing of Metakaolin- and GBFS-Based Geopolymers: A Sustainable Technology Aligned with the European Green Deal - Gokcegoz, Yusuf; Uysal, Mucteba; Canpolat, Orhan; Arikan, Oktay; Dilbas, Hasan; Aygun, Beyza (MDPI, 2025)
On-site curing of metakaolin (MK)- and granulated blast furnace slag (GBFS)-based geopolymer mortars remains a major bottleneck compared to thermal treatment for early strength development, and electrical curing is proposed here as a highly scalable and energy-efficient alternative technology. Geopolymer mortars with 0-100% MK/GBFS binder ratios were activated using sodium silicate (SS) and sodium hydroxide (SH) solutions of the following molarities: 6, 8, 10, 12, and 14 M. Steel fiber (SF), carbon fiber (CF), waste erosion wire (EW), and carbon black (CB) microfiller were incorporated to enhance the electro-conductive efficiency of the geopolymer matrix. Specimens were subjected to electrical curing under 10 V and 20 V AC and were compared with benchmarking under ambient conditions of 23 degrees C and thermal conditions of 70 degrees C. The findings established that the incorporation of fibers substantially boosted the level of conductivity and mechanical performance, with 28-day compressive strengths of up to 88.30 MPa (0.50% EW, 20 V) and flexural strengths of up to 22.24 MPa (0.50% CF, 7 days), exceeding the results of conventional curing in various instances. Microstructural studies based on well-bonded geopolymer gels with fibers indicated uniform geopolymerization through electrical curing without deleterious fiber-matrix interactions. A multi-criteria decision support approach (the HD method) based on 273 parameters established 0.50% CF, 0.75% SF, 0.75% EW, and 1.00% CB as the group-wise optima and chose 0.75% EW as the single-best performing combination. The findings confirm that electrical curing is a low-carbon, cost-effective, and field-adjustable curing technology with the potential to achieve target strength ratings, in line with the European Green Deal's climate-neutral building material goals.
Keywords: carbon black; carbon fiber; electrical conductivity; erosion wire; multi-criteria decision support; WASTE EROSION WIRES; CARBON-BLACK; FIBER; CEMENT; CONDUCTIVITY; TEMPERATURE; STRENGTH; PROFILE; Chemistry; Materials Science; Metallurgy & Metallurgical Engineering; Physics